AGAMA, ETIKA DAN ETOS KERJA DALAM AKTIVITAS EKONOMI MASYARAKAT NELAYAN JAWA - Mochammad Nadjib (Jurnal Ekonomi dan Pembangunan, 2025)
Religious practices of Javanese fishermen, who majorities are Moslems, have been strongly influenced by the ancestors’ thought. Ritual of sea give alms, offerings and “black magic” are some activities showing its dependence on the supernatural powers. On the other hand, even though they have a high work ethos, fishermen are widely perceived as the poorest society. This article is mainly intended to discuss the fishermen’s belief in relation to their work ethos. The hypothesis is that even though most of the fishermen have a high work ethos, but they do not behave as what their religion has been taught. This article is written based on the literature studies as well as the various knowledge accumulations of some primary researches on the fishermen life. Review of literature studies is purposed to understand the concept of the religion in assessing work ethics and work ethos. Meanwhile, primary data was obtained from a series of studies that has been conducted on the fishermen community in the north and southern coast of Java. Indication, loose understanding of the religion values and ethics are the essential factors which expressed the behavior and character of the fishermen to have permissive attitude, extravagant with money and wasteful.